A sense of belonging - John Stevens (Oxford University Press, 1989)
The stories that make up A Sense of Belonging have been chosen for their variety of style and theme, providing students with the opportunity to examine different writing models and techniques. A Sense of Belonging begins with a comprehensive account of the basic elements of short story writing (theme, characterisation, plot, setting and style), and gives students a step-by-step guide to writing their own short stories. Each story is accompanied by a selection of carefully graded activities which range from straightforward